Symposium 3: Learning nests and local habitations: Locations for networked learning - Jones, Chris; Healing, Graham (Proceedings of the International Conference on Networked Learning, 2010)
In this paper, we return to two descriptions of the ways that learning is located in technology enhanced environments. The idea of a local habitation arose in the context of an ecological view of the way people shaped new technologies for their own needs and it stood in opposition to the idea that new media and technologies led to inevitable consequences. The second term learning ‘nests’ arose out of research that focused on student study-bedrooms. Both terms were useful in humanising the relationships between new networked technologies and their users and locating the students and teachers who made use of them. We revisit the idea of learning nests understood as a local habitation using data collected as part of an ESRC funded project examining The Net Generation encountering e-learning at university. The report is based on 19 first year undergraduate students who took part in a cultural probe exercise. During 24 hours they received SMS text messages and recorded answers to a fixed set of prompt questions either using a small hand held video camera or using a small notebook. Our findings illustrate how students give meaning to the array of technologies and services they are presented with. They show that the technological landscape has changed markedly in the past 10 years but that student practices do not seem to have moved as quickly. Students still use the kinds of learning spaces they used 10 years ago despite the increased availability of network access to the Internet and the increased ownership and availability of mobile devices. An area where there has been significant change is in the social character of students’ engagements with networked technologies and the integration of the mobile phone, social networking and other social technologies into the everyday fabric of student life. However there is little evidence of significant change in student practices in terms of the adoption of mobile network access from this research and this should lead to caution in making predictions of change.